Marketing Strategies of the Horticultural Production Chain - Palma, Marco A. (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book consists of a series of articles that present novel trends in horticulture marketing and some of the key supply chain management issues for the horticulture industry across a wide range of geographical regions.